ХIХ ƏСИР ҚАРАҚАЛПАҚ ƏДЕБИЯТЫНДА ИМПРОВИЗАЦИЯ ДƏСТҮРИ (Күнхожа, Əжинияз ҳəм Бердақ дөретиўшилиги мысалында) - Матимов, Қ.Г. (ILIM hám JÁMIYET, 2023)
The article examines the tradition of improvisation in the works of the great poets of the Karakalpak literature of the 19th century Kunkhodzha, Ajiniyaz and Berdak. In the literature of this period are studied syncretic principles of artistic forms. In the works of poets, the traditions of improvisation are theoretically described. The great representatives of the Karakalpak literature of the 19th century Kunkhoja, Ajiniyaz and Berdak are considered poets-improvisers.